PEMBELAJARAN BERBASIS IT APLIKASI PROGRAM MS.ACCES UNTUK MENINGKATKAN PEMAHAMAN MAHASISWA PADA POKOK BAHASAN INVENTARISASI - Nina Oktarina; Agung Kuswantoro (Universitas Negeri Semarang, 2011)
The purpose of this study was to determine the effectiveness of IT-based learning application program Ms. Access in improving students’ understanding on the subject of an inventory of supplies management courses. Competence standards is considered successful if the student has the following indicators (a) at least 75% of students scored at the end of seventy (b) the activity and attention of students during the learning process increases. As for the professor, is considered successful when the learning management capabilities increase. This research is a class act. The research was carried out in vocational education administration office with a time of study for 6 months. The number of students is one of a number of study groups 54 people. The results demonstrate the application of IT-based learning program Ms Acces very effective in increasing student understanding of the subject inventory. It also increases the activity and attention of students during the learning process and learning ability of lecturers in the subject of inventory management. Advice related to the results of this study are: (1) At the time of implementing IT-based learning application program on the subject of Ms Access inventory of facilities and infrastructure should support such as the Internet network must already exist and are connected properly, (2) In order to optimize the learning process, lecturer at the beginning of lectures should give examples of using the program in advance to students with a coherent phase.